2002
DOI: 10.1086/340839
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High‐lying Levels on Atomic Models Relevant to Spectroscopic Analyses of Solar Extreme‐Ultraviolet Spectra

Abstract: In this work we investigate the effect of including high-lying configurations in the collisional-radiative models used to calculate spectral line intensities recorded by the Solar Ultraviolet Measurement of Emitted Radiation (SUMER) spectrometer on board the SOHO satellite. Many of the emission lines observed by SUMER are attributed to transitions within the L and M electronic shells of ions isoelectronic to sequences from Li i to Na i. By using atomic data that are mostly generated by the Hebrew University La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Energies for these were taken from Moore (1971), Corliss & Sugar (1982) and Shirai et al (1987) for Ar viii , Fe xvi and Ni xviii , respectively, and Sampson et al (1990) for all other ions. Test calculations including higher‐lying levels were found to have a negligible effect on the theoretical line ratios considered in this paper, as also found by Doron et al (2002).…”
Section: Adopted Atomic Data and Theoretical Line Ratiossupporting
confidence: 83%
See 1 more Smart Citation
“…Energies for these were taken from Moore (1971), Corliss & Sugar (1982) and Shirai et al (1987) for Ar viii , Fe xvi and Ni xviii , respectively, and Sampson et al (1990) for all other ions. Test calculations including higher‐lying levels were found to have a negligible effect on the theoretical line ratios considered in this paper, as also found by Doron et al (2002).…”
Section: Adopted Atomic Data and Theoretical Line Ratiossupporting
confidence: 83%
“…In summary, our analysis of the SERTS data sets reveal generally very good agreement between theory and observation for the Na‐like ion transitions present in the spectra, indicating that the lines are reliably detected and are not seriously affected by blending. Most of the Na‐like ion emission features may therefore be employed with confidence in solar spectral analyses, such as abundance studies (Doron et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Even larger enhancement factors were measured in a CMEproducing active region, i.e., first ionization potential enhancements of 7-8 compared with the usual factor of 3-4 (Ciaravella et al 2002). Atomic physics parameters used in solar physics have been steadily improved, by measurements of the resonance strengths and energies for dielectronic recombination (Savin & Laming 2002), high-lying electronic shells (Doron et al 2002), escape probabilities and absorption factors (Fischbacher et al 2002), modeling of observed S xii and Fe xxi lines (Keenan et al 2001(Keenan et al , 2002a(Keenan et al , 2002b, Fe xiii lines (Landi 2002), and Fe xxv (Dzifcakova & Kulinova 2001). Major progress cumulated in the fourth release and update of the atomic database CHIANTI (Landi et al 2002a(Landi et al , 2002b, which contains atomic data over the entire wavelength range of A ˚.…”
Section: Elemental Abundances and Atomic Physicsmentioning
confidence: 99%
“…In O iv the required excitation energy for the 2p 3 levels is $32 eV, whereas for the 2s2p 2 levels it is only $16 eV. A good aspect of the line ratios we have chosen is that the upper levels in the numerator, 2p 3 , are not populated significantly by cascades, at least not at temperatures close to the temperature of the ion maximum abundance (Doron et al 2002). This is a distinct advantage because, normally, level populations resulting from weak excitations are more sensitive to other mechanisms such as cascades.…”
Section: The N III and O Iv Atomic Systemsmentioning
confidence: 99%